Characteristics, reactivity and source apportionment of ambient volatile organic compounds (VOCs) in a typical tourist city. (15th October 2019) - Zhang, Xufeng; Yin, Yuanyuan; Wen, Jianhui; Huang, Shilei; Han, Deming; Chen, Xiaojia; Cheng, Jinping
Abstract: Currently, studies on the characteristics, reactivity and source apportionment of volatile organic compounds (VOCs) are mainly focused on large cities, however, information about the source characteristics of VOCs in less-developed regions is insufficient. In this study, ambient air samples ( n = 352) were collected from 11 sampling sites (including urban areas, suburban areas, outer suburb areas, and background areas) in Guilin, a typical tourist city located in southwest China, during the period 1st May to 30th November 2018 to determine the concentrations, temporal and spatial distribution, and activity of VOCs and to identify their sources. The results showed that the concentration of VOCs was 23.67 ± 9.77 ppbv, and aromatics were the most abundant VOCs, accounting for 65.75% of the total VOCs concentrations. The propylene-equivalent concentration and the ozone formation potential (OFP) of VOCs were 10.08 ppbv and 158.02 ppbv, respectively, and aromatics contributed the largest, accounting for 88.87% and 93.00%, respectively. Moreover, the ratios of T/B and X/E were 1.44 ± 0.92 and 0.74 ± 1.10, respectively. The temporal and spatial distribution of VOCs showed that there were significant differences of the VOCs concentrations between seasons (higher in autumn and lower in summer) and the VOCs concentrations were both high in urban areas and outer suburb areas. Based on the positive matrix factorization (PMF) method, 5 sources were identified as fuel evaporation, vehicle exhaust, industrial productions, solvent use, and biogenic emissions, contributing 35.32%, 28.29%, 15.65%, 11.20%, and 9.54%, respectively. Results indicated that a high proportion of aromatics in ambient VOCs and a large contribution of aromatics to O3 generation are the main characteristics that differentiate Guilin as a typical tourist city from other types of cities. We concluded that the VOCs in Guilin mainly come from the emissions of fuel evaporation and vehicle exhaust, and the impact of industrial emissions is relatively small, which is consistent with the characteristics of a tourist city. Moreover, our results revealed that the aging degree of air mass in Guilin is relatively higher than other cities, which inferred that the VOCs in Guilin may be affected by transmission from external sources. Graphical abstract: Image 1 Highlights: First time continuous observation of ambient VOCs in a typical tourist city. The temporal and spatial distribution characteristics of ambient VOCs were examined. Aromatics were the most abundant VOCs and the largest contributors to OFP. Fuel evaporation made the largest contribution to ambient VOCs.